SARS-CoV-2 Remained Airborne for a Prolonged Time in a Lockdown Confined Space - Xinyue Li; Xiao Qi; Jianxin Ma; Yang Pan; Tian Tian; Yue Zhang; Zhen Li; Wenjing Li; Lingli Sun; Lu Zhang; Zheng Zhang; Quanyi Wang; et al. (Aerosol and Air Quality Research)
Abstract Airborne transmission of COVID-19 plays an important role for the pandemic. However, nucleic acid based evidence of direct association of COVID-19 with environmental contamination is lacking. Here, we investigated a COVID-19 outbreak with two fast food employees infected, in which a traveler despite of a 14-day quarantine turned positive after check in with a hotel, using environmental SARS-CoV-2 sampling, epidemiological tracing, viral RNA sequence as well as surveillance method. Out of 25 positive environmental air and surface swab samples (N = 237) collected, SARS-CoV-2 was found to have remained airborne (5640–7840 RNA copies m−3) for more than 4 days in a female washroom. After aging for 5 days in the air, no viable virus was detected. The traveler did not have any contacts with the two employees; however, genome sequencing showed that SARS-CoV-2 variants from three patients and two environmental surface samples belonged to 20B viral clade, sharing a nucleic acid identity of more than 99.9%. We concluded that the outbreak was triggered by SARS-CoV-2 contaminated environments, where the employees inhaled the virus from the air or touching facility surfaces where the traveler did not have any physical contacts with.